Mucocutaneous Leishmaniasis/HIV Coinfection Presented as a Diffuse Desquamative Rash. (8th December 2014) - da Silva, Guilherme Almeida Rosa; Sugui, Daniel; Nunes, Rafael Fernandes; de Azevedo, Karime; de Azevedo, Marcelo; Marques, Alexandre; Martins, Carlos; Ferry, Fernando Raphael de Almeida
Abstract : Leishmaniasis is an infectious disease that is endemic in tropical areas and in the Mediterranean. This condition spreads to 98 countries in four continents, surpassing 12 million infected individuals, with 350 million people at risk of infection. This disease is characterized by a wide spectrum of clinical syndromes, caused by protozoa of the genus Leishmania, with various animal reservoirs, such as rodents, dogs, wolves, foxes, and even humans. Transmission occurs through a vector, a sandfly of the genus Lutzomyia . There are three main clinical forms of leishmaniasis: visceral leishmaniasis, cutaneous leishmaniasis, and mucocutaneous leishmaniasis. The wide spectrum of nonvisceral forms includes: localized cutaneous leishmaniasis, a papular lesion that progresses to ulceration with granular base and a large framed board; diffuse cutaneous leishmaniasis; mucocutaneous leishmaniasis, which can cause disfiguring and mutilating injuries of the nasal cavity, pharynx, and larynx. Leishmaniasis/HIV coinfection is considered an emerging problem in several countries, including Brazil, where, despite the growing number of cases, a problem of late diagnosis occurs. Clinically, the cases of leishmaniasis associated with HIV infection may demonstrate unusual aspects, such as extensive and destructive lesions. This study aims to report a case of mucocutaneous leishmaniasis/HIV coinfection with atypical presentation of diffuse desquamative eruption and nasopharyngeal involvement.